The Burlington Magazine for Connoisseurs (voortgezet als : The Burlington Magazine (vanaf: 1948-)) - Fry, Roger; Read, Herbert; Nicolson, Benedict (Londen : The Savile Publishing Company, 1903)
The magazine was established in 1903 by a group of art historians and connoisseurs which included Roger Fry, Herbert Horne, Bernard Berenson, and Charles Holmes. Its most esteemed editors [2] have been Roger Fry (1909–19), Herbert Read (1933–39), and Benedict Nicolson (1948–78). The journal's structure was loosely based on its contemporary British publication The Connoisseur, which was mainly aimed at collectors and had firm connections with the art trade. The Burlington Magazine, however, added to this late Victorian tradition of market-based criticism new elements of historical research inspired by the leading academic German periodicals and thus created a formula that has remained almost intact to date: a combination of archival and formalist object-based art historical research juxtaposed to articles on collectors’ items and private collections, enlivened with notes on current art news, exhibitions and sales.[3] The lavishness of this publication almost immediately created financial troubles and in January 1905[4] Fry embarked on an American tour to find sponsorship to assure the survival of the journal,[5] which he had quickly recognized as a magazine for the developing study of art history. (https://en.wikipedia.org/wiki/The_Burlington_Magazine)
Online: https://www.burlington.org.uk/ en https://archive.org/search.php?query=burlington%20magazine
Https://en.wikipedia.org/wiki/The_Burlington_Magazine
Online: https://www.jstor.org/journal/burlmagaconn
Engels
Tijdschriften